Antibiotic use and associated factors in a large sample of hospitalised older people. (December 2019) - ,; Mannucci, Pier Mannuccio; Nobili, Alessandro; Tettamanti, Mauro; Pasina, Luca; Franchi, Carlotta; Corrao, Salvatore; Marengoni, Alessandra; Salerno, Francesco; Cesari, Matteo; Perticone, Francesco; Licata, Giuseppe; et al.
Highlights: Hospitalised older people are frequently prescribed with antibiotics. Physical dependence and corticosteroid use are associated with increased antibiotic use. The use of antibiotics is also associated with an increased risk of in-hospital death. Abstract: Objectives: The aims of this study were to assess (i) the prevalence of antibiotic use, (ii) factors associated with their use and (iii) the association with in-hospital mortality in a large sample of hospitalised older people in Italy. Methods: Data were obtained from the 2010–2017 REPOSI register held in more than 100 internal medicine and geriatric wards in Italy. Patients aged ≥65 years with at least one antibiotic prescription during their hospitalisation were selected. Multivariable logistic regression models were used to determine factors associated with antibiotic use. Results: A total of 5442 older patients were included in the analysis, of whom 2786 (51.2%) were prescribed antibiotics during their hospitalisation. The most frequently prescribed antibiotic class was β- lactams, accounting for 50% of the total prescriptions. Poor physical independence, corticosteroid use and being hospitalised in Northern Italy were factors associated with a higher likelihood of being prescribed antibiotics. Antibiotic use was associated with an increased risk of in-hospital mortality (odds ratio = 2.52, 95% confidence interval 1.82–3.48) also when accounting for factors associated with their use. Conclusion: Hospitalised older people are often prescribed antibiotics. Factors related to poor physical independence and corticosteroid use are associated with increased antibiotic use. Being prescribed antibiotics is also associated with an increased risk of in-hospital death. These results demand the implementation of specific stewardship programmes to improve the correct use of antibiotics in hospital settings and to reduce the risk of antimicrobial resistance.